Bilingual Thematic Dictionaries - Stark, Martin (Lexicographica. Series Maior, 2011)
The series features monographs and edited volumes on the topics of lexicography and meta-lexicography. Works from the broader domain of lexicology are also included if they strengthen the theoretical, methodological and empirical basis of lexicography and meta-lexicography. Thevolumes focus on aspects of lexicography such as micro- and macrostructure, typology, history of the discipline, and application-oriented lexicographical documentation.